(untitled) (PerCursos, 2025)
This article discusses the use of toponymy as a didactic resource in Geography teaching, focusing on the municipalities of the Baixada Fluminense (BF). The proposal was developed in a workshop held at the Technical School of the Federal Rural University of Rio de Janeiro (CTUR), as part of the activities of the Pedagogical Residency Program in Geography at UFRRJ. The initiative targeted 11th-grade students, aiming to introduce them to the concept of place through active teaching-learning practices. To achieve this, the workshop employed cartography in a playful and participatory way, allowing students to become protagonists in the educational process. The study’s methodology combined bibliographic research, pedagogical practices, and social cartography, ensuring coherence between objectives and procedures. It was structured in three stages: first, students were introduced to the toponymic meanings of the municipalities of Baixada Fluminense; next, they assembled a puzzle, collaboratively creating a legend and symbols representing each municipality; finally, they participated in the joint construction of the regional map, discussing cartographic elements and deepening their critical understanding of the territory.The results indicated that the activity fostered critical reflections on the history and identity of the region, contributing to the deconstruction of stereotypes associated with the Baixada Fluminense. Moreover, it encouraged a broader and more contextualized geographical perspective, aligned with the Freirean conception of education as an emancipatory practice. Thus, the use of toponymy proved to be a powerful tool to integrate content, cartographic practice, and civic awareness.